مقارنة الموجودات الشعاعية بالموجودات التنظيرية في أمراض الجيوب الأنفية - يوسف يوسف; محمود عزيز; اسبر لينا (Latakia University Journal -Medical Sciences Series, 2019)
شملت هذه الدراسة 68 مريضا ً راجعوا العيادة الأذنية في مشفى الأسد الجامعي باللاذقية، 33 أنثى (49%) و35 ذكراً (51%). تم تقييم شكاية المرضى وانتقاء من توجه شكايته إلى مرض في الجيوب الأنفية وإخضاعهم لفحص سريري دقيق بالأدوات التقليدية. ثم إجراء تنظير تشخيصي بالمنظار الصلب ضمن العيادة. أجرى كل من المرضى بعدها تصويراً مقطعياً محوسباً للأنف والجيوب الأنفية. وأخيراً قمنا بمقارنة الموجودات المرضية في كل حالة واستخلاص النتائج النهائية. أظهرت الدراسة دور كل من التنظير الصلب والتصوير المقطعي المحوسب، وميزات أحدها على الآخر عند تشخيص آفات الجيوب، كما بينت الدراسة أن التنظير الصلب أساسي في التشخيص أما التصوير المقطعي فهو وسيلة مكملة. This study included 68 patients of otolaryngology clinic visitors to Al-assad University Hospital, Lattakia, Syria, 33 of whom were females (49%) and 35 males (51%). After the evaluation of their complaint, we chose those who had symptoms indicating a nasal sinus lesion. Then we performed a traditional nasal examination, including anterior and posterior rhinoscopy. We then preformed then performed a diagnostic nasal rigid endoscopy. All the patients underwent a sinonasal computed tomography imaging. At the end a comparison was made between the clinical findings in each case, and the final results were obtained. Our study demonstrated the role of the rigid diagnostic rhinoscopy and the computed tomography imaging in the diagnosis of sinonasal diseases, showing the advantages of the two. Radiologic imaging is a complimentary to the clinical and endoscopic evaluation of sinonasal disease patients, but it is not the primary way to diagnose this entity. This diagnosis is made clinically with the help of rigid endoscopy.